2021
DOI: 10.1080/2578983x.2020.1819092
|View full text |Cite
|
Sign up to set email alerts
|

Incarcerated people’s challenges for digital inclusion in Finnish prisons

Abstract: The digitization of society creates both challenges and opportunities for prisons. Previous studies show that prisons' digitization affects interaction between incarcerated people, prison culture and reduces recidivism, however it also poses security risks. In this study, we ask how do barriers to digital inclusion appear among incarcerated people in the prison context, and how do they perceive whether face-to-face interactions with employees can be replaced by digital services. The analytical starting points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Several studies have also shown the central importance of age from the perspective of digital inclusion [ 49 , 50 ]. The significance of age has also been observed in studies of prisoners’ digital skills [ 27 , 30 ]. Thus, this study also examines the effect of prisoners’ age on the intention to use digital health care and social welfare services.…”
Section: Methodsmentioning
confidence: 93%
See 4 more Smart Citations
“…Several studies have also shown the central importance of age from the perspective of digital inclusion [ 49 , 50 ]. The significance of age has also been observed in studies of prisoners’ digital skills [ 27 , 30 ]. Thus, this study also examines the effect of prisoners’ age on the intention to use digital health care and social welfare services.…”
Section: Methodsmentioning
confidence: 93%
“…According to Jewkes and Reisdorf [ 27 ], older prisoners, as well as long-term prisoners, are a group whose use of technology is associated with specific challenges, or even resistance, due to their incompetence. On the other hand, millennials are often accustomed to navigating digital society and, due to their young age, are very smooth users of digital services [ 30 ]. However, in this survey, age does not appear to be a relevant factor in terms of use intention, although it does have a significant effect on the sense of control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations